Dynamic Controller Instantiation in MEC-NFV based Software Defined Internet of Vehicles - Sabino, Atricia; Simoes, Rhodney; Dias, Kelvin (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2020: Anais Estendidos do X Simpósio Brasileiro de Engenharia de Sistemas ComputacionaisDO - 10.5753/sbesc_estendido.2020.13098, 2020)
Softwarization of vehicular networks has been a fundamental approach to deal with its dynamic topology along with requirements of scalability and flexible resource management in order to deploy future Internet of Vehicles (IoV). Despite Software-defined Vehicular Networks (SDVN) has gained momentum in industry and academia to tackle the aforementioned issues, some requirements such as on-demand allocation of network functions and scalability support are not yet satisfactorily addressed in current proposals. Even scalable solutions based on distributed and hierarchical SDN controllers are commonly deployed statically before the network operation. With the advent of network functions virtualization (NFV), it is expected that IoV will benefit from a standard architecture for dynamic instantiating of SDN controllers to provide an efficient solution for IoV management. This article proposes and evaluates a flexible and dynamic solution for the management of IoV through the synergy between SDN and NFV paradigms in order to provide on-demand instantiation of SDN controllers, as well as meet QoS requirements. The results demonstrate the effectiveness of the proposal in supporting the increasing demand for connected vehicles, reduction in packet loss, jitter control, and avoiding processing overhead when compared to the performance of traditional architecture.